2005
DOI: 10.1002/qre.670
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Reliability Prediction of 935 nm LEDs Using Failure Laws and Low Acceleration Factor Ageing Tests

Abstract: Numerous papers have already reported various results on electrical and optical performances of GaAs-based materials for optoelectronic applications. Other papers have proposed some methodologies for a classical estimation of reliability of GaAs compounds using life testing methods on a few thousand samples over 10 000 hours of testing. In contrast, fewer papers have studied the complete relation between degradation laws in relation to failure mechanisms and the estimation of lifetime distribution using accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 42 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…In particular, optical power variation mechanism of InGaN/GaN LEDs should be characterized by two different working zones limited by the threshold current (I th ) [13]. When current is lower than a threshold value, typically <10 mA, optical power will exhibit a quadratic increase with current.…”
Section: Theoretical Modeling Of Emitted Optical Power For High-pmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, optical power variation mechanism of InGaN/GaN LEDs should be characterized by two different working zones limited by the threshold current (I th ) [13]. When current is lower than a threshold value, typically <10 mA, optical power will exhibit a quadratic increase with current.…”
Section: Theoretical Modeling Of Emitted Optical Power For High-pmentioning
confidence: 99%
“…Nowadays, few mathematical models of optical power are presented for LED devices, especially the model of optical power relation with junction temperature and injection current. An experimental method was conducted to characterize optical power for commercial InGaAs/GaAs LEDs [13]. In this paper, optical current curve is measured by two different current working zones.…”
Section: Introductionmentioning
confidence: 99%
“…Current-voltage characteristics can particularly provide suitable information about transport of electrical carriers inside the active zone [6]. A semiconductor analyser (Keithley 236) was used to observe gradual changes in current-voltage before and after irradiations.…”
Section: Electrical and Optical Characterisationsmentioning
confidence: 99%
“…Numerous papers have reported that temperature and/or high current injection lead to more than two different failure mechanisms in optoelectronic devices [1], significantly reducing device performance parameters such as efficiency, output power, and lifetime; degradation laws used in this case are then exclusively empirical. The actual integration of optoelectronic devices in space mission is difficult because of the sensitivity of these devices regarding radiations.…”
Section: Introductionmentioning
confidence: 99%